ANALISIS PERILAKU KEUANGAN MAHASISWA YANG DIPENGARUHI OLEH LITERASI KEUANGAN DAN PENDAPATAN ORANG TUA - Pulungan, Delyana Rahmawany (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
The purpose of the authors of this research is to determine the effect of financial literacy and parents' income on the financial behavior of students of Management Study Program, Faculty of Economics and Business, Muhammadiyah University of North Sumatra. The sample in this study were 100 respondents who were students of Management Study Program, Faculty of Economics and Business, Muhammadiyah University of North Sumatra. The results of this study were collected through a questionnaire which was processed and analyzed using Multiple Linear Regression. Then perform a data quality test using the validity test using the Corrected Item. Total and reliability test using Cronbach Alpha. To test the hypothesis in this study the researcher used the t test and f test and conducted the coefficient of determination test. The results of this study indicate that the financial literacy variable shows a positive influence on the financial behavior variable as shown by t count 7,730, while the t table is 2,872 and a significance value of 0,000 <0.05, there is a positive influence of the parent's income variable on student financial behavior as shown by t count. 2,627 while the t-table is 2,872 and the significance value is 0,000 <0.05, and for financial literacy and parents' income, it has a significant influence on the financial behavior of Management Study Program students, Faculty of Economics and Business, Muhammadiyah University of North Sumatra with a value of Fcount of 67,630> Ftable of 3.09 and a significant value of 0,000 which is smaller than 0.05. Furthermore, the R-Square value obtained is 0.574, indicating about 57.4% of the influence of financial literacy and parents' income on student financial behavior.